UPAYA PENINGKATAN PENGETAHUAN TENTANG ANEMIA PADA REMAJA PUTRI DI SMAN 1 SOROPIA, KABUPATEN KONAWE - Rosnah, Rosnah; Rofiqoh, Rofiqoh; Risma, Risma; Kasim, Syaifudin Suhri (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2024)
Adolescent girls are a group at higher risk of developing anemia compared to adolescent boys with a prevalence in Indonesia of 26.5%. One of the causes of these nutritional problems is a lack of knowledge about anemia. Efforts that can be made to reduce the problem of anemia are by providing nutrition education. The implementation of this nutrition education aims to increase adolescent girls' knowledge about anemia. This nutrition education was carried out at SMAN 1 Soropia with 30 young women as subjects. The method used in this nutrition education is the counseling method with presentations about iron deficiency anemia using pocket books, PowerPoint, and two-way discussions. and the results of nutrition education were tested using the paired t test.   This community service program was carried out by a team of lecturers from the Nutrition Department, Health Polytechnic, Ministry of Health, Kendari, involving students. This activity will be carried out in September 2024.  The results showed that the nutritional knowledge score increased from 80.8 to 87.7, there was a significant difference (p<0.05) in the knowledge score about anemia before and after counseling.  These results indicate that nutrition education using pocket books can increase knowledge about anemia in adolescent girls.